2016
DOI: 10.1111/eff.12306
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic versus functional diversity metrics: how do fish communities respond to anthropogenic stressors in reservoirs?

Abstract: Biological indicators are frequently used to assess the effects of anthropogenic stressors on freshwater ecosystems. The structure of fish communities and their response to stressors have been commonly described by taxonomic richness, diversity and evenness. More recently, functional structure of communities has also been suggested to be a reliable indicator of disturbance. This article aimed at testing whether taxonomic and functional diversity metrics can provide comparable or complementary information on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 72 publications
(141 reference statements)
1
16
0
2
Order By: Relevance
“…Here, we found that elevation range was an important driver of richness of the three considered facets similarly to what was found in several taxa of vertebrates (Meynard et al 2011, Sagouis et al 2017. Elevation range seems to be a more integrative surrogate for the overall diversity of environmental conditions over the river catchment than the area of the catchment.…”
Section: Drivers Of Freshwater Fish Diversity Patterns In Europesupporting
confidence: 76%
“…Here, we found that elevation range was an important driver of richness of the three considered facets similarly to what was found in several taxa of vertebrates (Meynard et al 2011, Sagouis et al 2017. Elevation range seems to be a more integrative surrogate for the overall diversity of environmental conditions over the river catchment than the area of the catchment.…”
Section: Drivers Of Freshwater Fish Diversity Patterns In Europesupporting
confidence: 76%
“…stocking, fishing). This summary enlightens the importance of moving towards a trait-based approach to get a mechanistic understanding of the effects of impoundment on fish communities (see Lima et al 2016bLima et al , 2018Sagouis et al 2017;) and to detect more subtle impacts in fish communities (i.e. changes in assemblage that occur before species loss).…”
Section: Mechanistic Understanding Of the Effects Of Impoundment On Fmentioning
confidence: 99%
“…Earlier works have provided valuable information regarding the effects of dams on fish communities, but the divergences observed regarding fish responses to impoundment call for a global assessment that goes beyond taxonomic indices to include fish assemblage metrics and functional indices (Mérona & Vigouroux ; Mims & Olden ; Lima et al , ; Sagouis et al ; Santos et al ). Moreover, the effects brought about by dams and newly created reservoirs might also vary across latitudes according to the inherent adaptability of fish communities to respond to the physico‐chemical and biological changes (Rosenberg et al ; Gomes & Miranda ; Vörösmarty et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, traditional taxonomic-based diversity metrics fail to respond to changes in community structure resulting from environmental disturbances, for example, in the case of species invasions (Sagouis, Jabot, & Argillier, 2016). As such, incorporating multiple diversity metrics into conservation strategies can provide a more robust and systematic framework for conservation resource allocation (Strecker, Olden, Whittier, & Paukert, 2011).…”
Section: Introductionmentioning
confidence: 99%